Rumination-focused cognitive behaviour therapy for non-responsive chronic depression: an uncontrolled group study. Issue 3 (18th October 2019) - Moeller, Stine Bjerrum; Austin, Stephen F.; Hvenegaard, Morten; Kistrup, Morten; Gran, Stine; Watkins, Ed
Abstract: Background: One-third of patients with depression do not respond satisfactorily to treatment, and approximately 20% of all patients treated for depression develop a chronic depression. One approach to more effective treatment of chronic and treatment-resistant depression is to target rumination – an underlying mechanism implicated in the development and maintenance of depression. Aim: The purpose of this uncontrolled group study was to investigate the feasibility of individual rumination-focused cognitive behavioural therapy (RfCBT) for patients with chronic and treatment-resistant depression. Method: A total of 10 patients with chronic and treatment-resistant depression were offered 12–16 individual sessions of RfCBT. The primary outcome was depressive symptoms as measured by Hamilton Depression Scale at pre-, post- and 3-month follow-up. Secondary symptoms measured included self-reported rumination and worry. Results: There was a significant reduction in depressive symptoms ( p < 0.05), rumination ( p < 0.01) and worry ( p < 0.5) from pre- to post-treatment. Half of the participants ( n = 5) showed significant reliable change on levels of depressive symptoms post-treatment. The reduction in depressive symptoms, rumination and worry were maintained at follow-up. Conclusions: RfCBT was associated with significant reductions in depressive symptoms in a small sample with chronic and treatment-resistant depression. Despite limitations of being a small uncontrolled study with limited follow-up, these results are promising in a difficult to treat population. RfCBT warrants further systematic evaluation.